Tubulin β‐III modulates seizure activity in epilepsy. Issue 3 (17th May 2017) - Xu, Xin; Shangguan, Yafei; Lu, Shanshan; Wang, Wei; Du, Chao; Xiao, Fei; Hu, Yida; Luo, Jing; Wang, Liang; He, Changlong; Yang, Yong; Zhang, Yanke; et al.
Abstract: Tubulin β‐III (TUBB3) is the most dynamic β‐tubulin isoform expressed in neurons, and is highly expressed in the central nervous system. However, the relationship between TUBB3 and epileptic seizures has not been thoroughly investigated. The aims of this study were to investigate the expression of TUBB3 in patients with temporal lobe epilepsy and two different rat models of chronic epilepsy, and to determine the specific roles of TUBB3 in epilepsy. TUBB3 expression was upregulated in human and rat epileptic tissue. Moreover, TUBB3 expression was associated with inhibitory GABAergic neurons and the inhibitory postsynaptic scaffold protein gephyrin. TUBB3 downregulation attenuated the behavioural phenotypes of epileptic seizures during the pilocarpine‐induced chronic phase of epileptic seizures and the pentylenetetrazole kindling process, whereas TUBB3 overexpression had the opposite effect. Whole‐cell clamp recordings and western blotting revealed that the amplitude of GABA‐A receptor‐mediated miniature inhibitory postsynaptic currents and the surface expression of the GABA‐A receptor were increased in rats in which TUBB3 expression was downregulated. Importantly, TUBB3 interacted with GABA‐A receptor‐associated protein, which is known to be involved in GABA‐A receptor trafficking. These results indicate that TUBB3 plays a critical role in the regulation of epileptic seizures via GABA‐A receptor trafficking, suggesting a molecular mechanism for new therapeutic strategies. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.